Income tax grouping as tax management tool: Lessons from EU with focus on Poland - Andrzej Karpowicz (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The paper discusses the availability tax grouping among EU countries as well as benefits and costs of this tax incentive. Article focuses on Poland, where real usage of this tax management tool is analysed. Grounds for its (low) popularity are investigated. Analysis was made primarily based on observation of values and time trends build on data published by Polish Ministry of Finance, Statistical Yearbooks, PwC reports and Eurostat. Although tax grouping for corporate income tax purposes is offered by half of EU Member States, Poland is the only CEE country that offers this tax allowance. However, Polish corporations rarely use it in practice. Reasons include elevated entry requirements, lack of VAT grouping, low corporate income tax rate, lack of additional withholding tax benefits, no possibility of tax losses utilization, profitability requirements or retroactive duties in case of losing a status of a tax group. Those obstacles seem to outweigh the benefits of higher net return on capital, decreased transfer pricing requirements, higher liquidity and limited tax compliance burden. Those limited gains are prized primarily by biggest Polish entities, which indeed use tax grouping. The novelty and value of this paper lies in analysis of important topic from practical perspective, which was not thoroughly verified before both in Poland but also in other jurisdictions. It may also serve as a hint for managers considering entrance in a tax group and policymakers, while amending tax law regulations.
Keywords: H21; H25; K34; 650; income tax; tax management; taxation; return on equity; tax grouping; business tax